2021
DOI: 10.1038/s41598-021-86755-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation reference genes for qRT-PCR normalization in different cultivars during fruit ripening and softening of peach (Prunus persica)

Abstract: Quantitative real-time PCR (qRT-PCR) has been emerged as an effective method to explore the gene function and regulatory mechanisms. However, selecting appropriate reference gene (s) is a prerequisite for obtaining accurate qRT-PCR results. Peach is one of important fruit in Rosaceae and is widely cultivated worldwide. In this study, to explore reliable reference gene (s) in peach with different types during fruit ripening and softening (S1–S4), nine candidate reference genes (EF-1α, GAPDH, TBP, UBC, eIF-4α, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…Our results provided further evidence that the expression of reference genes varied between varieties and that there was a need to conduct reference gene screening for different trials. Meanwhile, we also found that in addition to GAPDH, ACT1 and ACT2 also presented good stability between different varieties of kiwifruit, which was in agreement with recent studies that ACT was the most stable gene between different varieties of peach [34] and jujuba [35]. Both ACT1 and UBQ maintained stable transcript levels in kiwifruit stimulated by different hormones (or pollen polysaccharide), which was similar to the results of a previous study about bananas [36].…”
Section: Discussionsupporting
confidence: 91%
“…Our results provided further evidence that the expression of reference genes varied between varieties and that there was a need to conduct reference gene screening for different trials. Meanwhile, we also found that in addition to GAPDH, ACT1 and ACT2 also presented good stability between different varieties of kiwifruit, which was in agreement with recent studies that ACT was the most stable gene between different varieties of peach [34] and jujuba [35]. Both ACT1 and UBQ maintained stable transcript levels in kiwifruit stimulated by different hormones (or pollen polysaccharide), which was similar to the results of a previous study about bananas [36].…”
Section: Discussionsupporting
confidence: 91%
“…These results show that TEF2 is not the best normalization factor for different genotypes. It is possible that the different varieties of peach and experimental conditions have led to the discrepancy between the two assays [ 13 ]. The poor stability of TEF2 was also pointed out in peach and other species.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the selection and validation of reference genes in plants [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. However, these reference genes exhibit constant expression patterns under certain experimental conditions, but their expression levels vary widely under other experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR reaction specificity was assessed by the presence of a single peak in the dissociation curve after amplification and through size estimation of the amplified products by agarose electrophoresis. Normalized gene expression levels were measured by the relative standard curve procedure using the geometric mean of two reference genes, Actin and Sand-like (Lloret et al, 2017;You et al, 2021). Results were the average of 3 technical replicates each one.…”
Section: Ii35 Gene Expressionmentioning
confidence: 99%